IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA SISWA KELAS III SDN KEBONSARI KULON 1 KOTA PROBOLINGGO - Mohammad Triya Reza Putra; Didit Yulian Kasdriyanto; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Curriculum changes in Indonesia, especially the implementation of the Independent Curriculum, are an innovative step in an effort to improve the quality of 21st century education. One of its implementations is through the Pancasila Student Profile Strengthening Project (P5) which is designed to shape students' character according to Pancasila values. This study was motivated by the importance of understanding how P5 is implemented at the Elementary School level, especially in grade III which has just implemented the Independent Curriculum in the 2024/2025 academic year at SDN Kebonsari Kulon 1, Probolinggo City. This study aims to examine in depth the implementation process of P5, which includes aspects of preparation, implementation, and assessment. The approach used is descriptive qualitative, data collection techniques through observation, interviews, and documentation. The main data sources come from grade III teachers and the principal as key informants. The main focus of this study is on P5 activities with the theme